Las estrategias virtuales de aprendizaje y su influencia en la comunicación educativa en la Unidad Educativa Prócer José de Antepara de la ciudad de Vinces - Elage Solis, Beatriz Alexandra (2022)
The coronavirus pandemic (COVID-19) has caused an unprecedented crisis in all areas, including education. Communication develops differently than in a face-to-face context, in which there are without exception affects that determine the nature of the relationship between teachers and students and promote or hinder the learning process. For this reason, the following scientific problem is posed, how do virtual strategies affect communication? To answer it, the research objective is presented: Determine the influence of virtual learning strategies in educational communication. The development of the research is presented with a quantitative approach, a descriptive cross-sectional study, as a sample 100 students and 40 teachers were taken, which corresponds to the total population. The questionnaire was created by the authors. The results of the analysis showed that there are many limitations that both students and teachers have to face, which requires technical training so that the teaching-learning process in virtual environments can be carried out efficiently and effectively.